Reading-to-Writing Mediation model of higher-order literacy - Ahmed, Yusra; Kent, Shawn C.; Keller-Margulis, Milena (Frontiers in Psychology, 2023)
Writing problems are comorbid with reading problems. Further, reading is implicated in some aspects of writing (e.g., reviewing and editing). Despite what is known, however, there remain significant barriers to understanding the nature of reading-writing relations, as few studies are comprehensive in the number and types of literacy skills evaluated. This study consists of a secondary data analysis of two studies employing structural equation modelling (SEM) to evaluate relations among reading and writing components skills independently, using the Direct and Inferential Mediation Model (DIME) of reading comprehension and Not-so-Simple View of Writing (NSVW) as theoretical frameworks. We evaluate relations between reading and writing components from these models with a sample of upper elementary students with/at-risk for learning disabilities (n = 405). Lower-order components included word reading, vocabulary, handwriting and spelling. Higher-order components included background knowledge, reading strategies, inferencing, planning, editing, and revision. The literacy outcomes were oral and silent reading fluency, reading comprehension, and writing quality and productivity. We systematically build a Reading-to-Writing Mediation (RWM) model by first merging the DIME and NSVW components in a direct effects model (Aim 1), expanding the joint model to include reading and writing fluency (Aim 2), evaluating indirect effects among DIME and NSVW component skills (Aim 3), and finally, evaluating indirect effects with reading and writing fluency (Aim 4). The findings suggest that higher order fluency and comprehension skills are differentially related to writing activities and products. The pattern of results help elucidate the mechanisms of how various reading and writing skills transfer and relate. The results have implications for targeted and implicit instruction in multicomponent interventions and the use of screeners to identify areas of risk.